2005
DOI: 10.1002/er.1114
|View full text |Cite
|
Sign up to set email alerts
|

The effect of condenser heat transfer on the energy performance of a plate heat pipe solar collector

Abstract: SUMMARYFor a novel prototype solar collector, using a plate heat pipe, condenser heat transfer was analysed in detail. The condenser has the shape of a rectangular channel. Flow and heat transfer of water in the rectangular channel was modelled and the heat transfer coefficient assessed, using the Fluent code. Under typical operating conditions a mixed convection situation occurs. The channel is inclined and heating is through one wall only (upper channel surface). The range of temperature differences consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Results showed that the Nusselt number is significantly higher than the one for forced convection in a rectangular channel with fully developed boundary layers. In order to enhance heat transfer, a modification to the rectangular channel was analyzed, using baffles to improve flow distribution and increase velocity [18]. Azad [19] investigated theoretically and experimentally the thermal behavior of a gravity assisted heat pipe solar collector.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the Nusselt number is significantly higher than the one for forced convection in a rectangular channel with fully developed boundary layers. In order to enhance heat transfer, a modification to the rectangular channel was analyzed, using baffles to improve flow distribution and increase velocity [18]. Azad [19] investigated theoretically and experimentally the thermal behavior of a gravity assisted heat pipe solar collector.…”
Section: Introductionmentioning
confidence: 99%